Cultured Mast Cells from Patients with Asthma and Controls Respond with Similar Sensitivity to Recombinant Der P2‐Induced, IgE‐Mediated Activation. (12th September 2013) - Krohn, I. K.; Sverrild, A.; Lund, G.; Dahl, R.; Erjefält, J. S.; Backer, V.; Hoffmann, H. J.
Abstract The function of cultured mast cells may depend on genetic or environmental influence on the stem cell donor. This study investigates whether asthma or atopy in the donor influenced the growth and sensitivity of mast cells cultured from patients with asthma and healthy controls under identical conditions. Mast cells were cultured from peripheral blood from twelve patients with an objectively confirmed asthma diagnosis and eight healthy subjects. During the last 2 weeks of culture, mast cells were incubated with IL‐4 and 80 kU/l recombinant human IgE containing two clones (7% + 7%) specific for mite allergen Der p2. The sensitivity of IgE‐mediated activation of mast cells was investigated as FcεRI‐mediated upregulation of CD63. Ten subjects were atopic, defined as a positive skin prick test (>3 mm) to at least one of ten common allergens. After activation with recombinant Der p2, the maximum CD63 median fluorescence intensity was 20 456 ± 1640 (SE) for patients with asthma and 22 275 ± 1971 (SE) for controls (ns). The fraction of CD63 positive cells was 54.4% in patients with asthma and 48.4% in controls (ns). The allergen concentration inducing 50% of the maximal CD63 response was similar in patients with asthma [−0.4795 log ng/ml ± 0.092 (SE)] and controls (−0.6351 log ng/ml ± 0.083, ns) and in atopic and non‐atopic subjects. When cultured, sensitized and activated under identical conditions, mast cells from allergic asthmatics and healthy controls respond similar. Activation of cultured mast cells appears to depend on culture conditions (IL‐4, IgE) rather than on donor status as atopy and asthma.